Potential New Modes of Treatment of Neurotrophic Keratopathy. Issue 11 (November 2015) - Unknown
Abstract : Abstract: The cornea focuses external light onto the retina, a function for which it must be transparent and possess a smooth surface. Homeostasis of the corneal epithelium is regulated by various humoral factors present in the tear fluid and by neural factors derived from the trigeminal nerve. Neurotrophic keratopathy (NK) is characterized by corneal epithelial disorders that result from impairment of trigeminal nerve function and a consequent deficiency of neural factors. The ideal mode of treatment for this condition is the regeneration of damaged trigeminal nerve fibers, but such therapy is not currently available. In this review, we describe established and potential new treatments of NK. Our research demonstrated that a combination of the neurotransmitter substance P and insulin-like growth factor 1 (IGF-1) has a synergistic stimulatory effect on corneal epithelial migration in vitro and on corneal wound closure in vivo. Furthermore, we identified the minimal amino acid sequences of substance P and IGF-1 required for this synergistic action based on the assumption that the clinical application of peptides corresponding to these sequences would have fewer side effects compared with the full-length molecules. Combination of the substance P-derived peptide FGLM-amide and the IGF-1-derived peptide SSSR promoted corneal epithelial wound healing in patients with NK. Clinical Trial Registration —URL:http://www.clinicaltrials.gov . Unique identifier: NCT01756456.